Green analytical methodology using indian almond (terminalia catappa l.) leaf extract for determination of aluminum ion in waste water from ceramic factories - Pimporn Insain (2018)
The use of natural reagents from plant extracts for chemical analysis is one of the approaches in the development of low cost and environmentally friendly green analytical chemistry methodology. Here, crude extract from Indian Almond (Terminalia Catappa L.) leaves was used for colorimetric determination of aluminum by monitoring the absorbance of the Al 3+ -extract complex at 435 nm. Dry leaves and freeze-dried fresh leaf extract can be kept for extended use. A simple flow injection analysis (FIA) system was also employed for rapid analysis (approximately 180 injections/h). The linear working range up to 100 mg L -1 was established with a detection limit (blank + 3SD) of 0.8 mg L -1 , a limit of quantitation (blank + 10SD) of 2.4 mg L -1 , and a relative standard deviation of 3 - 5%. This simple green analytical chemistry methodology was applied for the determination of Al 3+ in waste water samples from ceramic factories. The results agreed well with the results obtained from the ICP-OES technique. © 2013 The Japan Society for Analytical Chemistry.